KARAKTERISTIK FISIK, KIMIA DAN ORGANOLEPTIK MIE KERING PADA BERBAGAI RASIO TEPUNG BONGGOL PISANG KEPOK - Asnani Asnani; Abdul Rahim; Ifall Ifall (AGROINTEK, 2019)
This work deals with the effect of banana (sweet plaintain or ‘kepok’ variety) hump flour substituted to wheat flour in the making of noodle, on physical, chemical, and sensory characteristics of noodle.  A completely randomized was employed, with three replicates. Sensory analysis was conducted according to randomized group design. Four proportions of banana hump to wheat flour (10:90, 20:80, 30:70, and 40:60, weight basis) was studied. Results showed that the best physical and chemical characteristics was shown by noodle made from 10:90 proportion of banana hump to wheat flour, with 4.59% water absorption, 0.57% cooking loss, 10.37% water content, 34.21% starch content. However, result of sensory analysis suggested that the most liked noodle was that made from flour proportion of 20:80 with ‘like’ for colour, ‘like very much’ for aroma, ‘like’ for texture, ‘like’ for taste, and ‘like’ for overall preference